The understanding of plastic and reconstructive surgery amongst Queensland medical students. (June 2016) - Conyard, Christopher; Schaefer, Nathan; Williams, Daniel; Beem, Henry; McDougall, James
Abstract: The field of plastic and reconstructive surgery is a unique and poorly understood surgical subspeciality. There is a misunderstanding about the scope of the speciality amongst both the public and professionals. Medical schools provide a unique opportunity to educate future medical practitioners on the role of surgical subspecialities. Medical students at the Griffith University in Queensland, Australia, were invited to participate in a 30-question electronic survey to analyse their understanding of the surgical subspecialities. The students were asked to choose which surgical subspeciality would be most likely to treat the surgical condition. The five key areas of plastic and reconstructive surgery were included. The survey involved 234 medical students. In total, 115 (49%) students were in their clinical years, with 23 students having completed a rotation in plastic surgery. Of the hand, maxillofacial and reconstructive operations, the chances of a student selecting a plastic surgeon as the primary operator significantly improved if they had plastic surgery experience. Students were more likely to associate plastic surgeons with cosmetic procedures. This study has highlighted the gap between a medical student's perception and reality of the scope of Plastic and Reconstructive Surgery. It has emphasised the need for greater exposure and education in this surgical subspeciality if future medical practitioners are to better match the requirements of their patients to the skills of the specialist. If plastic surgeons wish to continue to be recognised as specialists in hand, craniofacial and reconstructive surgery, this gap between perception and reality needs to be addressed.